Risk Management For Sporting Events - Zemikael Getu; Sisay Mengistu (Publikasi Indonesia, 2022)
Risk management is one of the primary responsibilities of event organizers, yet so often ignored or misunderstood, particularly by inexperienced planners, because, like my now-paranoid event-goers, one can’t envision what one has not been exposed to – they don’t know what they don’t know. This article will show you how and why risk management is a fundamental component of event management, and introduce you to the functions of risk management within the overall field of events management and the tools you may use to perform these functions effectively.